Korelasi antara Kemampuan Literasi Lingkungan dengan Sikap Peduli Lingkungan Siswa Kelas V SDN Kembangan Utara 07 Petang - Esa Agpriani; Harlinda Syofyan (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This research is motivated by the low environmental literacy skills of fifth grade students at SDN Kembangan Utara 07 Evening. This research was conducted to find out the correlation between the literacy abilities of students and the environmental care attitude of fifth grade students. The method used is correlational method with quantitative research. In this study, data collection was carried out using questionnaires. The sampling technique was used purposive sampling. The results in the study showed that tcount 3.752 > ttable = 2.052 with a significant 0.000 <0.05, it means Ha is accepted, thus the results of the study show that there is a positive correlation between environmental literacy ability and environmental care attitude with a coefficient of determination of 54,7% the rest is influenced by other factors.